PENGARUH MODEL PEMBELAJARAN NUMBERED HEADS TOGETHER (NHT) BERBANTUAN ALAT PERAGA TERHADAP PENINGKATAN HASIL BELAJAR IPAS SISWA KELAS IV SD - Nur Raida; Nur Azmi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The purpose of this study was to determine the effect of the Numbered HeadsTogether (NHT) learning model assisted by teaching aids on improving studentlearning outcomes in Natural and Social Sciences.This study used a quantitativeapproach with a quasi experimental design in the form of a non-equivalent controlgroup design. The study population was all fourth grade students totaling 40 people.The sample was determined through purposive sampling, namely 20 students ofclass IV-A as the control class and 20 students of class IV-B as the experimentalclass. The results showed the sig value. (2-tailed) of 0,000 < 0,05 then H0 is rejectedand Ha is accepted, so it can be concluded that there is an effect of the NumberedHeads Together (NHT) learning model assisted by props on improving studentlearning outcomes. The N-gain test shows an average of 0,663 which is in themedium category. The average N-gain percentage of 66,3% is in the moderatelyeffective category. Thus, the Numbered Heads Together (NHT) learning modelassisted by teaching aids is quite effective in improving the learning outcomes ofNatural and Social Sciences of fourth grade students of SD Negeri 22 Banda Sakti.